Partial alleviation of oxidative stress induced by gamma irradiation in Vigna radiata by polyamine treatment. (3rd August 2017) - Sengupta, Mandar; Raychaudhuri, Sarmistha Sen
Abstract: Purpose: Environmental changes generate free radicals and reactive oxygen species (ROS) resulting in abiotic stress in plants. This causes alterations in germination, morphology, growth and development ultimately leading to yield loss. Gamma irradiation was used to experimentally induce oxidative damage in an important pulse crop Vigna radiata (L.) Wilczek or mung bean. Our research was aimed towards augmentation of oxidative stress tolerance through treatment with a group of aliphatic amines known as polyamines. Materials and methods: We used sub-lethal doses of gamma irradiation to generate oxidative damage which was evaluated using Nitro blue tetrazolium (NBT) staining, total antioxidant activity, 1, 1-Diphenyl-2-picryl hydrazyl (DPPH) radical scavenging assay, proline content and lipid peroxidation. Changes in internal free polyamines and messenger ribonucleic acid (mRNA) expression of key rate-limiting S-adenosylmethionine decarboxylase (SAMDC) enzyme in polyamine biosynthetic pathway was studied using real-time polymerase chain reaction (PCR). Results: We observed increased oxidative damage with higher irradiation dose which was partially alleviated by putrescine treatment. Internal levels of putrescine and spermidine increased with 1 mM (50 and 100 Gy) and 2 mM putrescine treatment. Expression of SAMDC also increased with putrescine treatment. Conclusion: This study shows that treatment with putrescine can partially alleviate oxidative damage caused by gamma rays.